Spontaneous Rupture of a Choledochal Cyst. Issue 1 (17th January 2022) - Bandeira, Eduardo; Carneiro, Rita; Soares, Eugénia
Teaching point: Spontaneous perforation with biliary peritonitis is a rare complication of bile duct cysts which should be considered in a patient presenting with acute abdomen, ascites, and dilated biliary tree on imaging.